Free Higher Education in Mexico Based on Jurisdictional Trends - Campos Montejo, Rodolfo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To analyze the experience regarding the search for free higher education in Mexico, from the jurisdictional matter. MATERIALS AND METHODS: It was developed under the qualitative hermeneutics approach, through the analysis of the criteria issued by the Federal Judiciary regarding free Higher Education. RESULTS: Nine theses were found, published in the period of September 2014- January 2017 which directly addressed the issue of gratuity, it was until 2017 that the criteria or the principle of Human Right to Education was fully recognized through jurisprudence in Higher Education. CONCLUSIONS: The diagnosis on the trends of Human Right to Higher Education in concatenation with the principle of free education represents a basic x-ray of a complex, and structural challenge that will require a lot of effort so it can be achieved on the part of all the involved actors. It can be observed, that the tendency of the Judiciary Power has been to recognize free Higher Education through the control of conventionality with the treaties that have been signed in Mexico.